Tantangan Limbah Infeksius Corona Virus Disease 2019 (Covid-19) yang Berasal dari Rumah Tangga - Dwi Utami Farkhati; Surahma Asti Mulasari (JUMANTIK (Jurnal Ilmiah Penelitian Kesehatan), 2022)
The Coronavirus pandemic that has happened to date an affects different areas, one of which is the effect of Coronavirus on families, which results on a timescale of irresistible waste. The point of this study was to build information about overseeing Coronavirus debased waste at home. The technique utilized is an expressive quantitative exploration with one gathering pretest-posttest plan. The quantity of tests upwards of 26 individuals. Subsequently, people in general has perceived the overall side effects of Coronavirus and the means that families need to take with oversight as well as suspects, while the Coronavirus pervasion at home has expanded in pretest squander (84.6%) and post-test (96.1%), home organization of disease, there were individuals who didn't comprehend and diminished pretest (100 percent) while post-test (96.1%), and treatment of polluted waste with pretest results (77%) and post-test (69.2%). Therefore, it is essential to instruct the overall population by distributing local area strengthening exercises, locally posted banners or wellness authorities and online media. This is a work that can be made to expand information about overseeing Coronavirus debased waste at home